ANALISA BISNIS EKONOMI KREATIF ELEKTOR PARIWISATA UNTUK MENINGKATKAN KEPATUHAN WAJIB PAJAK (STUDI KASUS PADA PELAKU BISNIS EKONOMI KREATIF DI MALANG) - Susyanti, Jeni (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2017)
This study purpose is analysis of creative economy businesses actor of tourism sector in order to fulfill their tax compliance. This study uses a descriptive research approach. Populations are 46 creative economy businesses actor of tourism sector in Malang city. Because the population is relatively small, all population becomes samples. The collected data is analyzed through three stages: data reduction, data display and conclusions. Research results show that: (1) creative economy businesses actors of tourism sector in Malang city have most problems to sell goods on credit. In addition, most of employees can not make taxation administration. (2) most of creative economy businesses actor of tourism sector in Malang city aware to tax compliance. However, they can not fulfill tax obligations (low awareness level in taxation fulfillment).